ANALISIS SKENARIO SIMULASI PENERAPAN KUOTA KEDATANGAN TRUK EKSTERNAL MELALUI IMPLEMENTASI SISTEM RESERVASI TRUK DALAM RANGKA MENGURANGI WAKTU PUTAR TRUK EKSTERNAL DENGAN SIMULASI KEJADIAN DISKRIT - 'Azzam Shofiyuddin, Yusuf
Koja Container Terminal (TPK) is one of the container terminals operating at the Tanjung Priok port. The increase in port activity causes congestion at TPK Koja. The congestion level is measured by using the external truck total turnaround time parameter. Based on internal data, TPK Koja has a total turnaround time of 104.06 minutes for imported trucks and 45.01 minutes for export trucks. If analyzed more deeply, about 92% (for imported trucks) and 79% (for export trucks) of the total turnaround time of the total external trucks at TPK Koja is waiting time. The implementation of a truck reservation system was chosen as a solution to solve this problem. However, the implementation of this solution can cause waiting times for trucks outside the gate. The decision variables in the truck reservation system analyzed in this study are quotas and time window duration. The external truck waiting time outside the gate and the external truck turnaround time are used as the based quota and time window duration selection for all level stages of the truck reservation system implementation. The level stages of the truck reservation system implementation is determined based on changes in the distribution pattern of external truck arrivals into an ideal arrival pattern (the same pattern every time). Based on the simulation, 60 quota for import trucks and 55 quota for export trucks is obtained as well as different time duration is the optimal strategy for each stage of the truck reservation system implementation. By implementing a truck reservation system, TPK Koja was able to reduce the total value of external trucks by up to 73% for imported trucks and 64% for export trucks. In this study, the discrete event simulation (DES) methodology was used in system modeling to formulate problem solutions because of the dynamics of the Koja TPK system.